The Warlock - Nicholas Flamel
Winner of a Parents' Choice Silver Honor Award, 2012. Fans of the Secrets of the Immortal Nicholas Flamel series will be breathless in anticipation of this thrilling penultimate chapter in Sophie and Josh's adventures. The twins of prophecy have finally been divided. The end is near. In Alcatraz, Machiavelli and Billy the Kid are following the Elders' plans to unleash the monsters of Alcatraz on the city of San Francisco, triggering the end of the Humani race. In the Shadowrealm, warriors -including Scathach and Palamedes- have been summoned to travel back in time to destroy the lost city of Danu Talis. The island must fall to save the modern world. In San Francisco, Josh has chosen a side - and he will not stand with his sister, Sophie, or the Alchemyst, Nicholas Flamel. He has chosen to fight alongside John Dee and the mysterious Virginia Dare. Sophie must find her twin before the battle begins. If she fails, all is lost forever...